A case report of a sub-clinical necrotising lower limb infection secondary to pelvic anastomotic leak and chronic corticosteroid use. (September 2019) - Nowicki, Jake; Rego, Mariana; Dean, Nicola R.
Abstract: Anabolic steroids have attracted attention from the media with regard to misuse, but overuse of medically prescribed steroids also has a propensity to cause harm. Gluteal necrotising soft tissue infections are an uncommon presentation for plastic surgeons, and therefore, abdominal sources may be overlooked. We report a rare case of a 57-year-old male who presented with a necrotising lower limb infection on a background of long-term corticosteroid overuse and recurrent pelvic anastomotic leaks.